Lille krigsbarn: Et casestudie i politisk poesi, medieøkologi og begivenhedskultur - Mønster, Louise (Passage - Tidsskrift for litteratur og kritik, 2026)
This article examines two interrelated developments in Scandinavian poetry since 2010: its growing political engagement and its integration into a media-ecological, event-driven cultural circuit. As poetry has become more explicitly politicized and responsive to contemporary global, social, and identity-political issues, it has also moved beyond the traditional poetry collection, engaging with new aesthetic practices, publication formats, and modes of performance across digital and physical platforms. As a case study, the article focuses on the award-winning Danish poet Henrik Nordbrandt and his poem “Vuggevise” (“Lullaby”). Written in response to the European refugee crisis in 2015, the poem was first published as an occasional poem in the Danish newspaper Politiken and performed by Nordbrandt on the newspaper’s website. Since then, it has circulated widely across media platforms and been performed in a range of contexts. The article investigates how changing media conditions and the pervasive logic of event culture have reshaped political poetry and its capacity to intervene in public debate. It asks how political poems realize their potential across media and events, how expanded poetic formats affect poetry’s ability to act politically, and whether the lyric genre possesses particular affordances that make it especially suited to political engagement.